Peran Guru PAI Dalam Mengembangkan Kecerdasan Emosional Dan Spiritual Siswi Di SMK Sultan Agung 2 Diwek Jombang - Husna Mauidhoh; Khoirul Umam (JOURNAL SAINS STUDENT RESEARCH, 2024)
Teachers have an essential role in the success of student learning and also play an important role in developing students' emotional and spiritual intelligence. Because students are expected to develop their intellectual abilities, attitudes, and behaviour during the learning process, teachers strongly influence these aspects. This research focuses on the influence of PAI teachers on the emotional and spiritual intelligence of vocational school students. The focus of the research is: 1) what is the role of PAI teachers in developing the emotional and spiritual intelligence of students at SMK Sultan Agung 2 Diwek Jombang?. 2) what are the supporting and inhibiting factors of PAI teachers in developing the emotional and spiritual intelligence of students at SMK Sultan Agung 2 Diwek Jombang?. In this thesis, the research methodology used is a qualitative approach with the type of case study research. This study's data collection techniques were interviews, observation, and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, and conclusions drawn. The results of this study are as follows: 1) the role of PAI teachers in developing emotional and spiritual intelligence is very important. PAI teachers themselves are like their biological parents who always provide advice and motivation, PAI teachers provide counseling services and train social skills for all students while the role of PAI teachers to develop spiritual intelligence is by assisting congregational letter activities when at school and reading the Quran every morning and getting used to memorizing short letters then holding a Quran sermon program once a month. 2) The supporting factors for the development of student intelligence are the existence of education in schools that promotes an inclusive and tolerant cultural environment, the existence of character education, social support between teachers' peers and families, diverse learning experiences, good role models between teachers and other figures in students' lives. The inhibiting factors are the existence of an unsupportive family environment, lack of self-understanding, lack of development of spiritual values in education, traumatic experiences, lack of education and also students' self-understanding, socio-cultural pressures that occur..